Ordinary differential equations in the oscillation theory of partial half-linear differential equation - MARIK, Robert (Journal of mathematical analysis and applications, 2008)
In the paper we study the damped half-linear partial differential equation div ( A ( x ) ‖ ∇ u ‖ p − 2 ∇ u ) + 〈 b → ( x ) , ‖ ∇ u ‖ p − 2 ∇ u 〉 + c ( x ) | u | p − 2 u = 0 . Using radialization method we derive general oscillation results which allow to deduce new oscillation criteria for this equation from oscillation criteria for ordinary differential equations. Using careful radialization we improve several known oscillation criteria.